2016
DOI: 10.1021/jacs.5b13475
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Coated Carbon Nanotube Ring with Enhanced Raman Scattering and Photothermal Conversion Property for Theranostic Applications

Abstract: We report a new type of carbon nanotube ring (CNTR) coated with gold nanoparticles (CNTR@AuNPs) using CNTR as a template and surface attached redox-active polymer as a reducing agent. This nanostructure of CNTR bundle embedded in the gap of closely attached AuNPs can play multiple roles as a Raman probe to detect cancer cells and a photoacoustic (PA) contrast agent for imaging-guided cancer therapy. The CNTR@AuNP exhibits substantially higher Raman and optical signals than CNTR coated with a complete Au shell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
154
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 217 publications
(155 citation statements)
references
References 49 publications
0
154
0
1
Order By: Relevance
“…The enhancement of PA signal of the hybrid vesicle was confirmed by simulating the optical spectra and near-field distribution with the discrete dipole approximation (DDA) using the DDSCAT 7.3 program. In vivo experimental results demonstrated that the hybrid vesicle is an excellent candidate as both PA imaging probe and photothermal agent for cancer theranostics 30, 38…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of PA signal of the hybrid vesicle was confirmed by simulating the optical spectra and near-field distribution with the discrete dipole approximation (DDA) using the DDSCAT 7.3 program. In vivo experimental results demonstrated that the hybrid vesicle is an excellent candidate as both PA imaging probe and photothermal agent for cancer theranostics 30, 38…”
Section: Introductionmentioning
confidence: 99%
“…The photothermal effects (PTE) have already shown a variety of practical applications, such as photo‐therapy, biomedical imaging, catalysis, controlled‐release systems, photothermal melting of DNA, and solar steam generation . Tremendous efforts have been dedicated to photothermal materials stimulated by near infrared (NIR) laser . However, until now the PTE of the broadband absorber are still low .…”
Section: Introductionmentioning
confidence: 99%
“…Given gold nanodots' plasmonic resonance feature, Au nanodots on HCNs' surface promoted the absorption of light from NIR wavelength (750–1200 nm) (Figure E). NIR (808 nm; the wavelength of NIR laser used for all experiments) irradiation increased AuHCNs' temperature in a dose‐dependent manner, and was always approximately twofold higher than HCNs (Figure F; Figures S7 and S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%